PENGELOLAAN PEMBELAJARAN BAHASA INGGRIS MELALUI PERMAINAN GAMBAR THINGS AROUND US PADA SISWA SMK - Walia Walia Walia (UNIVERSITAS BENGKULU, 2016)
This study aims to determine students' increased activity by using techniques to manage learning game images are expected to be an increase in learning of teachers and students . The research method was classroom action research . The subjects were students of class X SMK Negeri 2 Bengkulu City. Results of the study are there is improve of student skill and studentactivity with the way the game image. The learning process more effective, efficient and enjoyable. Students can actively engage in learning activities . In other words, learning through play action impelmentasi images can improve the students' activities in the learning process.Keywords: learning, activity, game images